ASPECTS OF SECURING BIOMEDICAL INFORMATICS NETWORKS AND SYSTEMS - Ion BOLUN; Arina ALEXEI (Economica)
The peculiarities of biomedical informatics systems (HISs) and networks (HINs) from the point of view of cyber security are systematized. Based on the particularities in question and on some statistical data on healthcare cybercrimes, the acuteness of the advanced securing of HISs/HINs is estimated. Cyber security standards in the field, including those related to medical devices, briefly described in the paper, facilitate successful orientation in the multitude of aspects and requirements of cyber security in various practical situations. Also, the paper presents several specific solutions (depending on the case) for securing HISs/HINs proposed and implemented in the field at the global level are described. They can serve to define cyber security modalities in concrete cases. It is mentioned that the requirements of cyber security and, respectively, the implementation of the respective informatics means in biomedical informatics applications, systems, and networks to comply with them depend on each specific case.